Analisis Campur Kode Pada Novel Mukidi Karya Rizal Adlan Mustafa - Muhammad Al Fath (LPPM Politeknik Pratama, 2023)
The purpose of this study is to examine the mixed form of code contained in the novel Mukidi by Rizal Adlan Mustafa. This study used a type of qualitative descriptive research that was guided by words in novels. The subject of this study was the novel Mukidi by Rizal Adlan Mustafa and the object of research was a mixture of codes in the novel Mukidi by Rizal Adlan Mustafa. In collecting information, researchers use note-taking and listening techniques. And the analysis techniques used include the elimination of certain factors. Based on the research conducted, 28 documents were obtained from the results of the study, including: 3 code transfer words (mix code into), 4 code transfer data into sentences, 4 code mix data into sentences, 3 code mix data out, 13 code mix data outside sentences. A form of code that is encrypted using a mixture of several codes that repeat into one data. Rizal Adlan Mustafa's novel Mukidi uses a mixture of codes in Indonesian, Arabic, English, and Javanese.